2010
DOI: 10.2147/ijn.s9220
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal effect of iron oxide nanoparticles on Staphylococcus aureus

Abstract: Abstract:In order to study the effects of iron oxide (IO) nanoparticles on Staphylococcus aureus, IO nanoparticles were synthesized via a novel matrix-mediated method using polyvinyl alcohol (PVA). The IO nanoparticles were characterized by transmission electron microscopy and dynamic light scattering. Further, S. aureus were grown in the presence of three different IO nanoparticle concentrations for four, 12, and 24 hours. Live/dead assays were performed and the results provide evidence that IO/PVA nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Proposed nanostructures possess well-defined physicochemical properties and proven antibacterial activity. According to published literature [35][36][37], the proposed mode of antibacterial action of magnetic nanoparticles involves their contribution in the induction of oxidative stress, via generation of reactive oxygen species (ROS), as well as interference with the bacterial electron transport of the oxidation of NADH. Moreover, they possess the ability to disrupt the membrane of microorganisms via the formation of a pore or by the endocytosis based mechanism shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed nanostructures possess well-defined physicochemical properties and proven antibacterial activity. According to published literature [35][36][37], the proposed mode of antibacterial action of magnetic nanoparticles involves their contribution in the induction of oxidative stress, via generation of reactive oxygen species (ROS), as well as interference with the bacterial electron transport of the oxidation of NADH. Moreover, they possess the ability to disrupt the membrane of microorganisms via the formation of a pore or by the endocytosis based mechanism shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Proposed nanostructures possess well-defined physicochemical properties and proven antibacterial activity. According to published literature [35][36][37], the proposed mode of antibacterial action of magnetic nanoparticles involves their contribution in the induction of oxidative stress, via generation of reactive oxygen species (ROS), as well as Our previous studies [38][39][40][41] have shown that they interact in a synergistic or additive manner, with chemotherapeutic agents used in standard antimicrobial treatment, as well as with a representative of antimicrobial peptides that take part in the immune-defense process and with their synthetic mimetics. Here we describe how the presence of magnetic nanoparticles might lead to improving the antimicrobial properties of artificial saliva substitutes ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…A comparable effect of ferric oxide and chitosan-coated silver nanoparticles against various bacteria, e.g. S. aureus and P. aeruginosa, has been reported [21,22]. S53P4 granules are described as releasing sodium from its surface after contact with body fluids, thereby increasing the pH into the alkaline range.…”
Section: Platinum -S53p4mentioning
confidence: 76%
“…Antimicrobial resistance is an old and huge concern for public health systems, having grown rapidly in recent times, spreading the preoccupation to economics [92,[95][96][97]. The use of gold, silver, aluminum, and iron oxide as antimicrobials was previously proven [29,[98][99][100][101][102].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…These radicals may increase the ROS stress inside the microorganism's cells, leading to an inhibition of their growth and multiplication. ROS may damage the DNA in bacteria and also protein production [101,117,118].…”
Section: Antimicrobial Activitymentioning
confidence: 99%